Pembuatan Video Tutorial Avatar Dengan Teknik Glow In The Dark Make Up Look Pada Mata Kuliah Tata Rias Fantas - Agustiani Safitri, Charina (Universitas Negeri Jakarta, 2022)
ABSTRACT Charina Agustiani Safitri, Tutorial Videos Making Avatar Character With Glow In The Dark Make Up Look Technique in Fantasy Cosmetology Course, Final project: Jakarta Diploma 3 Cosmetology Study Program, Faculty of Engineering, Jakarta State University, 2022. Face painting glow in the dark is one of the popular media in the world of fashion, makeup, hair, tattoos and many others. In the process of making Avatar with the Glow In The Dark technique requires 3 main ingredients, including scar wax, Uv painting, and Led Uv Light. This research was conducted with the aim of helping the learning process and adding knowledge for researchers and readers in the Avatar tutorial video with the Glow In The Dark technique. The assessment of the Avatar video tutorial with the Glow In The Dark technique was carried out with feasibility tests by 2 experts, namely material experts and media experts with the following assessment aspects, including content aspects, visual aspects, audio editing, language aspects, and typographic aspects. Based on assessments with material experts and media experts.